刘宗周《人谱》的改过思想及工夫论 = The idea of reform cultivation in Liu Zongzhou’s "Renpu" - 林彦慧 Lim, Dorothea Yan Hui (2015)
自孔孟以来改过思想就不断地被讨论。到了刘宗周，改过思想则作为人身与心都必须投入且履行的工夫，也是优入圣域的基础工夫。此外，改过除了是人的道德实践，也作为人道德意识的一部分。这种道德意识在宗周的《人谱》里则体现出 一种道德精神现象。《人谱》主要可分为两个部分。第一个部分《人谱正篇》以证人为缘由，阐述人之所以为人是因为人会改过。除了反驳当时王门后学，尤其是王龙溪言心不重道德实践，宗周也批评袁了凡〈功过格〉为逐名利而作。为了纠正当时虚妄空说的 学术风气，宗周因此作《人谱》。〈纪过格〉、〈讼过法〉与〈改过说〉为第二个部分，则将过错细疏分类，并且阐述了具体的改过工夫。此外，宗周回到了孔孟最初以善本身作为人们行善的目的。结合宋明理学言至善具天理的心，宗周将改过视为一种在心上持续的工夫。除了在内在本心里作克念、存心工夫，也须持续吸取外在经验，内化于心。当一个人的心之独体能时刻因为改过工夫而处在至善至诚的状态时，那么他即是一个道德完人、亦或圣人。这种无须提醒都能克念改过，保持至善具理的心则可言是人的道德精神现象。因此，本文将集中探讨刘宗周在《人谱》里的改过思想与他具体改过的工夫。在改过的过程中，本文也试图探索他的道德意识如何能作为一种道德精神现象而存在。Since the era of Confucius and Mencius, the idea of reform cultivation (改过思想) has been continuously discussed. Until Liu Zongzhou (刘宗周), this idea was also deemed as an effort that a person has to put his or her entire body and mind in. It was also meant as the basic step for entering the sacred zone (圣域). Besides being a practice, reform (改过) is also part of human’s moral consciousness (道德意识). In Zongzhou’s “Renpu” (《人谱》), this moral conscious thus presents the phenomenon of one’s moral spirit (道德精神现象). “Renpu” can be discussed as two parts. “Renpu Zhengpian” as the first part, elaborates on why humans are deemed as human is due to the fact that they can reform. Besides the rebuttal on late-Ming’s Wang School Philosophy (王门后学), especially directed towards Wang Longxi (王龙溪), focusing on just the heart but not moral practice, Zongzhou also criticised Yuan Liaofan (袁了凡) on creating “Gong Guo Ge” (〈功过格〉) for the sake of pursuing fame and power. Hence, to correct late-Ming’s academic atmosphere, he created “Renpu”. “Ji Guo Ge” (〈纪过格〉), “Song Guo Fa” (〈讼过法〉) and “Gai Guo Shuo” (〈改过说〉) being the second part of “Renpu”, listed all kinds of wrong-doings and elaborated on the concise steps of reforming one’s wrongdoings. On the other hand, Zongzhou followed how Confucius and Mencius viewed kindness ( 善) as purely the reason of one’s kind act. Together with how Neo-Confucianism spoke of a heart that contain both all-good (至善) and heavenly principle (天理), Zongzhou viewed reform as a continuous practice that has to be done in one’s heart. Besides restraining thoughts (克念) and conserving one’s heart (存心) in one’s inner heart, one also has to absorb outer experiences consistently, and internalise these experiences into one’s inner heart. Once the “duti” (独体) of one’s heart is at the state of all-good and all-sincere (至诚), one is then a morally perfect person (道德完人), or a sacred person (圣人). When one does not need to be reminded but still practices to reform, then one presents a phenomenon of his or her own moral spirit. Therefore, this essay will be focusing on the discussion of the idea of reform cultivation in Liu Zongzhou’s “Renpu”. In the process of reforming, we will then discuss on what makes up the phenomenon of one’s moral spirit when looking at one’s moral consciousness.